Tubeimoside I Antagonizes Yoda1-Evoked Piezo1 Channel Activation - Liu, Silin; Pan, Xianmei; Cheng, Wenbin; Deng, Bo; He, Yu; Zhang, Lei; Ning, Yile; Li, Jing (Frontiers in Pharmacology, 2020)
Piezo1, a mechanosensitive Ca2+-permeable non-selective cationic ion channel protein, is involved in a wide range of biological processes and plays crucial roles in vascular development. However, the pharmacology of this protein is in its infancy. Yoda1, the first specific chemical activator of Piezo1 channels, can activate Piezo1 in absence of mechanical stimulation. Hence, we sought to identify inhibitors of Yoda1 from Traditional Chinese Medicine (TCM). Intracellular Ca2+ measurements were conducted in human umbilical vein endothelial cells (HUVECs), HEK 293T cells overexpressing TRPC5 and TRPM2 channels, as well as in CHO K1 cells overexpressing TRPV4 channels. We identified tubeimoside I (TBMS1) as a strong inhibitor of the Yoda1 response and demonstrated its selectivity for the Piezo1 channels. Similarly, Yoda1-induced inhibitory results were obtained in Piezo1 wild-type overexpressed cells, murine liver endothelial cells (MLECs), and macrophages. The physiological responses of TBMS1 were identified by isometric tension, which can inhibit Yoda1 relaxation of aortic rings. Our results demonstrated that TBMS1 can effectively antagonize Yoda1 induced Piezo1 channel activation. This study sheds light on the existence of Yoda1 inhibitors and improves the understanding of vascular pharmacology through Piezo1 channels.